The Social Roots of Contemporary Prejudice - Heylen, Ben; Pauwels, Lieven J.R. (International Journal of Criminology and Sociology, 2015)
Background: Evolutionary theory suggests prejudice may be a result of the evolution of human sociality. In this study, we investigate this claim by integrating theoretical insights of evolutionary theory with the well-established social psychological research on prejudice centering on Right Wing Authoritarianism (RWA) and Social Dominance Orientation (SDO) as the main predictors of prejudice. Method: First, we developed two different signaling scales, probing respondents’ propensity to signal group commitment in a genuine or deceptive way. We administered a questionnaire consisting of the two signaling measures, RWA, SDO and prejudice measures to 1380 students. Analysis of the data was done using structural equation modeling. Results: Our results indicate that genuine signaling of one’s commitment to the in-group is positively associated with RWA, and that deceptively signaling one’s commitment to the in-group is positively associated with SDO. Both RWA and SDO are positively related to prejudice. Conclusion: Our study is the first to empirically reveal the pro-social roots of prejudice using classical measurement instruments. The findings give rise to a new array of research questions.